2015
DOI: 10.5507/bp.2013.087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biochemical markers and bone mineral density in patients with chronic kidney disease stage 5D at the start of hemodialysis treatment

Abstract: Background. Patients with chronic kidney disease (CKD) have significant disorders of bone and mineral metabolism. In addition, they can also develop other bone disorders including osteoporosis. This study evaluated the bone mineral density (BMD) of patients at the start of hemodialysis treatment as well as the relationship between BMD and possible risk factors or biochemical markers. Methods. The study was performed in 82 patients (28 females, 54 males). BMD was measured by dual-energy X-ray absorptiometry (DX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(42 reference statements)
2
3
1
1
Order By: Relevance
“…Several studies are consistent with our study showing that BMD decreased as age increased [14,17,18]. The effect of gender on bone mass in hemodialysis is controversial [19,20]. We found that BMD was significantly lower in women at the total body.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies are consistent with our study showing that BMD decreased as age increased [14,17,18]. The effect of gender on bone mass in hemodialysis is controversial [19,20]. We found that BMD was significantly lower in women at the total body.…”
Section: Discussionsupporting
confidence: 91%
“…This result is known to be common in hemodialysis patients with CKD (11,16). This finding suggests the possibility of a significant number of hemodialysis patients with osteomalacia in our study.…”
Section: Discussionsupporting
confidence: 61%
“…Hemodialysis patients with CKD are affected by bone disease associated with CKD and also share similar risk factors for osteoporosis with the general population (9,34,35). It should be noted that this bone disorder is multifactorial and complex and BMD alone may not be adequate to characterize the bone disease associated with CKD (9,11). In the present study, there was no relation between BMD T scores with Ca levels.…”
Section: Mean ± Sd T (Fn) T (Th) T (Ls)contrasting
confidence: 49%
See 1 more Smart Citation
“…According to the NHANES study, the prevalence of osteoporosis in the general population with GF < 35 mL/min is 24% in women and 11% in men [39]. Recently, two Czech cross-sectional studies of similar Caucasian populations comprising subjects on haemodialysis or in the very early stages of hemodialysis treatment were published [40, 41]. The average TH T -score was -1.4 in both studies, while the average LS T -score was -0.5 and -0.3, respectively.…”
Section: Discussionmentioning
confidence: 99%